Des « brocarts appliqués » dans la sculpture savoyarde - Lelong Florence; Pouyet Emeline; Champdavoine Sophie; Guiblain Thomas; Martinetto Pauline; Walter Philippe; Rousselière Hélène; Cotte Marine (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The identification of « applied brocades » in painted sculptures from the Savoy Duchy, dated from 1480 to 1530, has motivated the development of an analytical process to allow a systematic characterization of those decorations. It combines macro- and micrometer surface observations, non-invasive analyses using portable instrumentation, and nondestructive analyses of micrometric samples using synchrotron radiation. This approach allowed identifying the motifs, techniques and materials used to manufacture the « applied brocades », thus unraveling local singularities. The results also determined degradation products from the original metallic tin foil, a key material that ensures the preservation of the 3 dimensions of the motifs.